2022
DOI: 10.3390/diagnostics12040926
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perception When Transitioning from Classic to Remote Assisted Cardiac Rehabilitation

Abstract: Cardiac rehabilitation is an individualized outpatient program of physical exercises and medical education designed to accelerate recovery and improve health status in heart disease patients. In this study, we aimed for assessment of patients’ perception of the involvement of technology and remote monitoring devices in cardiac recovery. During the Living Lab Phase of the Virtual Coaching Activities for Rehabilitation in Elderly (vCare) project, we evaluated eleven patients (five heart failure patients and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In a qualitative study, patients with chronic heart failure reported difficulties in using exercise monitoring tools, managing exercise data, and mastering monitoring knowledge during a based on home-based cardiac rehabilitation exercise. 47 Therefore, the relevant monitoring training should be completed to improve their exercise monitoring knowledge and self-management ability.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, patients with chronic heart failure reported difficulties in using exercise monitoring tools, managing exercise data, and mastering monitoring knowledge during a based on home-based cardiac rehabilitation exercise. 47 Therefore, the relevant monitoring training should be completed to improve their exercise monitoring knowledge and self-management ability.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed insights into the medical efficacy of the VC with a focus on the separate medical use cases can be found in Del Pino et al (2023), Seregni et al (2022), Busnatu et al (2022) and La ˘craru et al (2023).…”
Section: Pilot Phase -Dsr Cycle 3 -Focus On Clinical Outcomesmentioning
confidence: 99%
“…That is where cardiovascular rehabilitation comes in. Cardiovascular rehabilitation (CR) is a customized program that combines medical therapy and physical activity with medical education, in order to accelerate recovery and enhance the health status in people with heart disease [4]. The 2021 European guidelines' recommendations on CVD prevention in clinical practice underline that medication adherence and lifestyle modifications are crucial in secondary CVD prevention, which may be expanded and improved via CR programs, lowering the incidence of recurrent heart disease and the risk of overall mortality [5].…”
Section: Of 19mentioning
confidence: 99%